The emergence of the sporting director role in football and the potential of social network theory in future research. Issue 4 (2nd November 2018) - Parnell, Daniel; Widdop, Paul; Groom, Ryan; Bond, Alex
ABSTRACT: The commodified and highly competitive nature of professional football (soccer) has increased the professionalisation of organisational structures and management practices within clubs that enhance their competitive advantages within the labour market. This is a direct result of the financial rewards for success, and the potential cost of failure is significant. The utilisation of the Sporting Director position represents one strategy for organisations to improve both on and off-field performance success through maintaining organisational influence and control. Yet, the role is accompanied by a range of conceptual and operational misunderstandings. This commentary aims to examine the emergence of the Sporting Director and to offer some guidance on potential avenues for future research. Specifically, we consider, how social network theory might provide a theoretical framework to understand the role of the Sporting Director in practice better. To achieve this, this commentary is structured into five sections. First, we outline the role of corporate governance, senior executives and board membership, within organisational studies and the applicability of this for professional football. Second, we offer a contextual analysis of the business of professional football in Europe, and in particular its move towards globalisation and commodification. Third, we provide a current review of the Sporting Director role in professional football. Fourth, we explain the value of thinking relationally, using a social network approach, to better understanding the role of the Sporting Director within the global context. Finally, we offer some concluding thoughts and considerations surrounding the adoption of the Sporting Director role in England, and outline some potential research agendas concerning social network theory, and related concepts such as embeddedness, structural holes and the strength of weak ties.